Emozioni e teoria del giudizio: una prima ricostruzione (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The paper focuses on the effects of recent psychological findings on the theory of adjudication – putting emphasis on the role played by emotions in the decision-making process. Two different philosophical claims will be analysed, starting from the very famous topos of digestive justice: the idea that the decision-making process is completely predictable (determinism) versus the irrationality of the decision claimed by the realists. In the conclusion a non-naturalistic perspective will be sketched, aiming at including the novel knowledge arising from psychology – i.e. emotions are part of physiological process of decision-making.
Keywords: Law and Emotions; decision-making; digestive justice; Neurolaw